Portraying the Use of Facebook for Educational Purposes Among Female Undergraduates: Causes and Activities - Luke, Joice Yulinda (Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
This study describes the use of Facebook for educational purposes among female students. The study focuses on two main objectives. First, the study reveals the causes to use Facebook as educational platform. Second, the study depicts the learning activities which female students did with Facebook. To explore the findings, the study gathered the data from survey among twenty-one female students of Bina Nusantara University who were selected randomly. They were asked to complete the closed-ended Likert-scale questionnaires. Then, the data were quantified and analyzed descriptively. The results show that the main reason of female students to use Facebook for learning was its ease accessibility from anywhere with the respondents’ personal gadget. Finally, the research proved that female students were extremely used Facebook to post the writing assignments like stories and essays. Overall, the study significantly conveys the worth usages of social networking sites as Facebook for educational purposes.